EFFECTS OF ADMINISTRATIVE DISCONTINUITY ON MICROBASINS PROGRAM IN SAO PAULO - Neves Neto, Carlos de Castro [UNESP]; Hespanhol, Antonio Nivaldo [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2015)
The effects of administrative discontinuity on Sao Paulo state Microbasins Program are discussed. In the first edition of this program (2000-2008), the environment was prioritized, encouraging rural producers to adopt appropriate soil and water management practices (direct seeding, gallery forest recomposition, erosion control, installation of septic tanks). During the second edition of the program (2011-2015), called Sustainable Rural Development Project - Microbasins II, the focus was completely changed, prioritizing the market. The objective of the Hydrographic Microbasins Program, in its second edition, is to introduce the producer to a Business Plan so that he/she can commercialize his/her production in the market. The program discontinuity leads to interruption of activities, which generates disbelief by the farmers, makes it difficult for technicians to execute the public policy and reduces the number of assisted family farmers, becoming even more selective than its first edition.
Keywords: discontinuity; public policies; Microbasins Program; family farmer